LT

3/4-0,25-( 7/3+(-9/2) )-5/6

H24
14 tháng 7 2019 lúc 17:25

\(=(\frac{3}{4}-\frac{1}{4})-\frac{7}{3}+\frac{9}{2}-\frac{5}{6}=\frac{1}{2}+\frac{9}{2}-\frac{14}{6}-\frac{5}{6}=5-\frac{19}{6}=\frac{11}{6}\)

Kết bạn nha bạn

Bình luận (0)

Bài làm

       \(\frac{3}{4}-0,25-\left(\frac{7}{3}+\frac{-9}{2}\right)-\frac{5}{6}\)

\(=\frac{3}{4}-\frac{1}{4}-\left(\frac{14}{6}+\frac{-27}{6}\right)-\frac{5}{6}\)

\(=\frac{1}{2}+\frac{13}{6}-\frac{5}{6}\)

\(=\frac{3}{6}+\frac{13}{6}-\frac{5}{6}\)

\(=\frac{11}{6}\)

# Học tốt #

Bình luận (0)
KK
14 tháng 7 2019 lúc 17:43

3/4-0,25-(7/3+(-9/2) )-5/6

=3/4-1/4-(14/6+(-27/6) )-5/6

=1/2-(-13/6)-5/6

=3/6+13/6-5/6

=(3+13-5)/6

=11/6

Bình luận (0)
DL
14 tháng 7 2019 lúc 17:57

\(\frac{3}{4}-0,25-\left(\frac{7}{3}+\frac{-9}{2}\right)-\frac{5}{6}\)

\(=\frac{3}{4}-\frac{1}{4}-\left(\frac{14}{6}+\frac{-27}{6}\right)-\frac{5}{6}\)

\(=\frac{1}{2}+\frac{13}{6}-\frac{5}{6}\)

\(=\frac{3}{6}+\frac{13}{6}-\frac{5}{6}\)

\(=\frac{11}{6}\)

Good luck !!! Rất vui vì giúp đc bạn <3

Bình luận (0)